Karaeng Electability In Village Head Elections: A Review Of Patron-Client Relations And Capital Power In Bontomate’ne Village, Jeneponto Regency - A. Rahman, A. M. Fatwa; Armin, Armin; Ariana, Ariana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This study explores the role of Karaeng in local politics in Bontomate'ne Village, Jeneponto, to understand the relevance of traditional power in the context of a modern political system. The phenomenon studied involves the transition from traditional governance to modern bureaucracy, as well as the continued political dominance of Karaeng through a patron-client system and resource control. The objectives of this study are to identify how Karaeng maintain their political influence, analyze the inequality of resource control, and evaluate the role of economic, cultural, social, and symbolic capital in their political dominance. Data collection was conducted through in-depth interviews with 22 purposively selected informants. The conclusion of the study shows that Karaeng continue to play an important role in local politics despite the transition to a modern bureaucratic system. The patron-client system in Bontomate'ne Village shows inequality in resource control, with Karaeng having significant control over land and wealth. The mutually beneficial relationship between Karaeng and their followers strengthens Karaeng's political position, while economic, cultural, social, and symbolic capital supports the continuation of their political dominance in Jeneponto society.